2015
DOI: 10.1007/s11243-015-9946-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and molecular studies of half-sandwich arene ruthenium and Cp*Rh/Cp*Ir complexes containing (3-picolyl)thiourea derivatives as N,S-bidentate donor ligands

Abstract: Series of mononuclear complexes of arene Ru and Cp*Rh/Cp*Ir complexes containing (3-picolyl)thiourea derivative ligands, of general formulae [(g 6 -arene)Ru(L)Cl]Cl and [Cp*M(L)Cl]Cl {L = benzoyl(3-picoylyl)thiourea, arene = benzene (1); p-cymene (2) and M = Rh (3); Ir (4); L = 1,3-bis(3-picolyl)thiourea, arene = benzene (5); p-cymene (6) and M = Rh (7); Ir (8)}, have been synthesized and characterized by spectroscopic methods. X-ray crystallographic studies of complexes (2)-(5), (7), and (8) reveal a typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The M‐S bond lengths in neutral complexes are slightly longer than that of cationic complexes (Table S3). The M‐Cl bond lengths in these complexes shows no significant differences and was found to be in the range of 2.399–2.438 Å which are comparable with earlier reported complexes . The bond angle values S‐M‐Cl and Cl‐M‐Cl in neutral complexes ( 7 – 9 ) lay in the range of 87.7–95.5 ° (Table S3).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The M‐S bond lengths in neutral complexes are slightly longer than that of cationic complexes (Table S3). The M‐Cl bond lengths in these complexes shows no significant differences and was found to be in the range of 2.399–2.438 Å which are comparable with earlier reported complexes . The bond angle values S‐M‐Cl and Cl‐M‐Cl in neutral complexes ( 7 – 9 ) lay in the range of 87.7–95.5 ° (Table S3).…”
Section: Resultssupporting
confidence: 84%
“…When methyl group is at the para position of the pyridine ring such as in benzoyl (4‐picolyl) thiourea (L2) it acted as bidentate chelating ligand whereas when methyl group is at the ortho position of the pyridine ring as in benzoyl (6‐picolyl) thiourea (L3) it behaved as neutral monodentate ligand. Previously we have shown that when methyl group is at the meta position of the pyridine ring such as in benzoyl (3‐picolyl) thiourea it coordinated metal in a bidentate chelating manner . Complexes ( 4 , 5 and 6 ) also have the cationic species [(arene) M (L2)к 2 ( N,S ) Cl] [(arene) = p ‐cymene, M = Ru and Cp*, M = Rh and Ir] and counter anion chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bond distance of metal to the nitrogen atom in all the complexes is within the range, i. e., ∼ 2.088(3) to 2.198(5) Å (Table ). The complexes contain 2‐aminopyrimidine are showing M−N and M−Cl bond lengths longer than the complexes containing 2‐mercaptopyrimidine ligand which is identical to the earlier values reported in literature {[(arene/Cp*) 2 M 2 (μ‐L1)Cl 3 ] + where, L1=pyridine‐2‐carbaldehyde nicotinoyl‐hydrazone 2.152(6); [Cp*MLCl] + where, L=benzoyl(3‐picolyl)thiourea/1,3‐bis(3‐picolyl)thiourea 2.335(2)‐2.4027(11)} . The metal to chloride ion of complexes ( 1 , 2 ) is 2.3983(19) to 2.434(2) Å which is the normal distance in the metal chloride complexes .…”
Section: Resultsmentioning
confidence: 99%
“…Since the choice of ligands plays a crucial role in determining the biological properties of the complexes we decided to substitute aryl group with pyridyl group and determine the coordination properties of pyridyl thiourea derivatives. Previous studies in this laboratory have reported some half‐sandwich arene ruthenium, rhodium and iridium complexes with pyridyl thiourea ligands and in this study, we report the synthesis, structural and cytotoxic activity against cancer and non‐cancer cell lines in vitro of p ‐cymene ruthenium, Cp* rhodium and Cp* iridium complexes containing thiourea derivatives. Ligands used in the present study are shown in Chart 1.…”
Section: Introductionmentioning
confidence: 99%